Investigating the Interactions between Free Radicals and Supported Noble Metal Nanoparticles in Oxidation Reactions - Crites, Charles-Oneil (Université d'Ottawa / University of Ottawa, 2015)
This thesis studies the interaction between free radical species and supported noble metal nanoparticles (silver and gold) in the context of oxidation reactions. The peroxidation of cumene is the first reaction to be discussed and the difference in peroxidation product distribution using silver nanoparticles (AgNP) versus gold nanoparticles (AuNP) is examined. Specifically, cumyl alcohol is obtained as the major product obtained when using supported AuNP, whereas cumene hydroperoxide is favoured for AgNP. Such variations in product distribution are partially explained by the differences in the nanoparticle Fenton activity, where the TiO2 support was proposed to enhance such activity due to possible electron shuttling capabilities with the nanoparticle surface. Use of hydrotalcite as a support was found to minimize this characteristic, due to its insulator properties. The stability of hydroperoxide was tested in the presence of various others supports (activated carbon, Al2O3, ZnO, SiO2 and clays) with little success, with hydroperoxide exhibiting stability in the presence of HT. Using an oxygen uptake apparatus, the interaction of the cumyl peroxyl radical with the AuNP surface was demonstrated. Furthermore, this interaction promotes decomposition leading to the corresponding alkoxyl radical and subsequent hydrogen abstraction to form the observed cumyl alcohol product. The radical interaction with supported nanoparticles, and its reversibility appear different for gold and silver and accounts for a large part of the product distribution differences observed between AuNP and AgNP, as illustrated below. The peroxidation of ethylbenzene and propylbenzene was studied and revealed the participation of a reactive surface oxygen species due to the decomposition of peroxyl radicals on the nanoparticle surface. The reactive oxygen species was found to be transient in nature in the case of AuNP . Furthermore, this surface species was found to be an important participant in hydrogen abstraction leading to peroxide product formation. Finally, supported nanoparticle catalyzed tetralin peroxidation was investigated to determine the influence of temperature on the peroxidation product distribution and how changes in the reaction temperature can effect the radical-nanoparticle surface interactions.
Keywords: Gold Nanoparticle; Silver Nanoparticle; Free Radical Chemistry; Epoxidation; Peroxidation; Cumene